Instructional Media in Early Moral Education: A Systematic Review on the Cultivation of Religious and Moral Values in Children Aged 4–6 - Ramona, Nadia; Cholimah, Nur (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
In an era marked by moral uncertainty and the erosion of traditional value systems, early childhood education faces increasing pressure to cultivate ethical and religious foundations from a young age. This study systematically reviews the role of instructional media in instilling religious and moral values among children aged 4–6. Utilizing a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol and structured using the PICO framework, this review synthesizes findings from 20 empirical studies published between 2016 and 2024. The analysis identifies two dominant categories of media—traditional (e.g., puzzles, board games, local games) and audiovisual (e.g., animations, digital storybooks)—which are most effective when integrated with pedagogical strategies such as storytelling, ritual routines, and play-based learning. Instructional tools grounded in local culture and values not only enhance comprehension but also support identity formation and contextual moral internalization. The review further finds that many media interventions leverage constructivist and experiential learning models, promoting internalization through relatable and immersive experiences. However, gaps remain, particularly regarding longitudinal impact assessments and cross-contextual evaluations. The studies underscore the need for teacher professional development in media-based moral instruction, culturally responsive curriculum planning, and collaborative engagement among educators, curriculum developers, and community stakeholders. Limitations include the narrow temporal scope and inconsistencies in methodological rigor across studies. Future research is encouraged to adopt more robust, long-term, and culturally comparative designs to determine optimal combinations of media types and pedagogical techniques for sustained moral development in diverse educational settings.